Systemic Lupus Erythematosus: An Overview of the Disease Pathology and Its Management - Ali, Asad (Cureus, 2018)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with varied natural history and multisystemic involvement. The pathogenesis is multifactorial and complex precipitating the formation of autoantibodies. One of the main factors in SLE is the interaction between environmental triggers and genetic factors. Genome-wide association study technology has led to the identification of more than 80 loci which produce key proteins that lead to small pathophysiological changes and are associated with SLE. There has been an improvement in the management of the disease with newly standardized scores that have been validated in assessing disease activity and quality of life, and have helped in clinical care as well as research. The last five decades have seen a marked improvement in the prognosis of SLE, thanks to better general care and the development of newer immunosuppressive drugs, more specifically biological agents.